2017
DOI: 10.1038/nm.4305
|View full text |Cite|
|
Sign up to set email alerts
|

Thymosin α1 represents a potential potent single-molecule-based therapy for cystic fibrosis

Abstract: Cystic fibrosis (CF) is caused by mutations in the gene encoding the cystic fibrosis transmembrane conductance regulator (CFTR) that compromise its chloride-channel activity. The most common mutation, p.Phe508del, results in the production of a misfolded CFTR protein, which has residual channel activity but is prematurely degraded. Because of the inherent complexity of the pathogenetic mechanisms involved in CF —which include impaired chloride permeability and persistent lung inflammation—a multidrug approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 67 publications
2
93
0
Order By: Relevance
“…It has been reported that 24-hour treatment with Tα-1 causes an increase in the expression of mature (fully glycosylated) CFTR, paralleled by an increase in CFTR function and potentiation of CaCC activity (as evidenced by microfluorimetric and electrophysiological assays including short-circuit current measurements and patch-clamp analysis) (26). We tested Tα-1 on well-differentiated primary cultures of human bronchial epithelial cells from 3 different F508del homozygous subjects by using electrophysiological and biochemical techniques (Figure 1).…”
Section: Tα-1 Does Not Increase F508del-cftr Expression/function In Pmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that 24-hour treatment with Tα-1 causes an increase in the expression of mature (fully glycosylated) CFTR, paralleled by an increase in CFTR function and potentiation of CaCC activity (as evidenced by microfluorimetric and electrophysiological assays including short-circuit current measurements and patch-clamp analysis) (26). We tested Tα-1 on well-differentiated primary cultures of human bronchial epithelial cells from 3 different F508del homozygous subjects by using electrophysiological and biochemical techniques (Figure 1).…”
Section: Tα-1 Does Not Increase F508del-cftr Expression/function In Pmentioning
confidence: 99%
“…We wondered whether the lack of CFTR rescue observed in our laboratories using biochemical techniques could be due to the different antibody used as compared with Romani and collaborators (26), using CF3 antibody originally developed by Pier and collaborators (48).…”
Section: Tα-1 Does Not Alter F508del-cftr or Cacc Currents As Evidencmentioning
confidence: 99%
See 3 more Smart Citations